THE SURROGACY CONTRACT OF INDONESIAN CITIZENS BETWEEN THE LAW THAT SHOULD BE AND THE REAL - Selly Eka Damayanti,; Putu Samawati Saleh; KN Sofyan Hasan (Fakultas Hukum Universitas Komputer Indonesia, 2026)
The practice of surrogacy in Indonesia has no clear legal basis and is generally considered illegal because it conflicts with legislation, religious norms, and social ethics. In fact, there has been an increase in the participation of Indonesian women becoming surrogate mothers through the online platform Find Surrogate Mother. Issues related to surrogacy agreements with surrogate mothers raise many legal uncertainties because the practice is carried out by Indonesian citizens but is illegal under the law. This study aims to examine the contractual framework of surrogacy by analysing the legal characteristics, validity, and implications of such contracts based on the principles of Indonesian civil law. This study uses a normative juridical method with a case study approach that focuses on the analysis of contract clauses and their legal consequences. The results of the study show that the contract between the surrogate mother, who is an Indonesian citizen, and the foreign couple is a private agreement that contains clauses on financial compensation, medical responsibility, confidentiality, and the transfer of child custody after birth. However, the contract is outside the jurisdiction of Indonesian law and contradicts the principle of legal protection for women as subjects of contracts. The findings of the study confirm the need to formulate national legal policies that regulate and restrict cross-border digital surrogacy practices, requiring the government to establish preventive and repressive measures in order to provide maximum legal protection for Indonesian citizens who are vulnerable to exploitation through international surrogacy contracts. Praktik sewa rahim (surrogacy) di Indonesia tidak memiliki dasar hukum yang jelas dan pada umumnya dianggap tidak sah karena bertentangan dengan ketentuan perundang-undangan, norma agama, serta etika sosial. Faktanya, terdapat peningkatan partisipasi perempuan Indonesia menjadi ibu oengganti melalui platform daring Find Surrogate Mother. Isu terkait perjanjian sewa Rahim terhadap ibu pengganti menimbulkan banyak ketidakpastian hukum karena praktiknya dilakukan oleh Warga Negara Indonesia (WNI) tetapi secara hukum illegal. Penelitian ini bertujuan untuk mengkaji kerangka kontraktual praktik sewa rahim dengan menganalisis karakteristik hukum, keabsahan, serta implikasi kontrak tersebut berdasarkan prinsip hukum perdata Indonesia. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan studi kasus yang menitikberatkan pada analisis klausul kontrak dan akibat hukumnya. Hasil penelitian menunjukkan bahwa kontrak antara ibu pengganti WNI dan pasangan asing merupakan perjanjian privat yang memuat klausul tentang kompensasi finansial, tanggung jawab medis, kerahasiaan, dan penyerahan hak asuh anak setelah kelahiran. Namun, kontrak tersebut berada di luar yurisdiksi hukum Indonesia dan bertentangan dengan prinsip perlindungan hukum terhadap perempuan sebagai subjek kontrak. Temuan penelitian menegaskan perlunya pembentukan kebijakan hukum nasional yang mengatur sekaligus membatasi praktik sewa rahim digital lintas negara, yang menuntut pemerintah untuk menetapkan langkah preventif dan represif demi memberikan perlindungan hukum maksimal bagi WNI yang rentan terhadap eksploitasi melalui kontrak sewa rahim internasional.